Contextualising coronavirus geographically. Issue 3 (8th June 2020) - Sparke, Matthew; Anguelov, Dimitar
Abstract : This editorial introduces a special virtual issue aimed at providing online access to articles that can contribute to the work of coming to geographical terms with the COVID‐19 pandemic. It outlines seven sub‐themes of enquiry and analysis that are especially useful for contextualising coronavirus geographically. These are explored in turn as geographies of: (1) infection, (2) vulnerability, (3) resilience, (4) blame, (5) immunisation, (6) interdependence, and (7) care. In each case, connections are made between publications that are included in the special virtual issue and other more recent writings related specifically to COVID‐19. In an effort to make these connections as useful as possible to geographers who have been drafted into online teaching in and about the pandemic, hyperlinks are used throughout to highlight additional online resources and reports. Abstract : This editorial introduces a special virtual issue of the RGS‐IBG journals aimed at providing online access to articles that can contribute to the work of coming to geographical terms with the COVID‐19 pandemic. It outlines seven sub‐themes of enquiry and analysis that appear especially useful for contextualizing coronavirus geographically. These are explored in turn as geographies of: (1) infection, (2) vulnerability, (3) resilience, (4) blame, (5) immunization, (6) interdependence and (7) care. The image is Mortality in 7 countries attributed to COVID 23/01‐20/O4, reproduced with kind permission of Danny Dorling from http://dannydorling.org/books/SLOWDOWN/Covid19.html .